Transient Mobility and Middle Class Identity : Media and Migration in Australia and Singapore - Gomes, Catherine (Springer Singapore : Imprint: Palgrave Macmillan, 2017)
This project offers an understanding of the transient migration experience in Asia through the lens of communication and entertainment media. It examines the role played by digital technologies and uncovers how the combined wider field of entertainment media (films, television shows and music) are vital and helpful platforms that positively aid migrants through self and communal empowerment. This book specifically looks at the upwardly mobile middle class transient migrants working in two of the Asia-Pacific's most desirable transient migration destinations - Australia and Singapore, providing a cutting edge study of the identities transient migrants create and maintain while overseas and the strategies they use to cope with life in transience.